HUBUNGAN PERDARAHAN GASTROINTESTINAL DENGAN LUARAN PASIEN STROKE ISKEMIK AKUT - Rico Defryantho,* Lisda Amalia,* Ahmad Rizal,** Suryani Gunadharma,* Siti Aminah,* Nushrotul Lailiyy (NEURONA, 2019)
INTRODUCTION GASTROINTESTINAL BLEEDING ASSOCIATED BY THE DELAY IN THE ADMINISTRATION OF ANTIPLATELET AND ANTICOAGULANT THUS AFFECTED THE CLINICAL OUTCOME AND PATIENT TREATMENT